Performance Analysis of Quantum Key Distribution B92 Protocol Using Qiskit - Prasetyo, Eko; Damarjati, Cahya; Mahmudi, Muhammad Nazih; Cahyadi, Eko Fajar (Jurnal Ilmiah Merpati (Menara Penelitian Akademika Teknologi Informasi); Vol 12 No 3 (2024): Vol. 12, No. 3, December 2024DO - 10.24843/JIM.2024.v12.i03.p05, 2024)
Quantum Key Distribution is a cornerstone of secure communication, utilizing quantum mechanics to achieve unparalleled security. This study evaluates the performance of the B92 protocol, a simplified scheme using non-orthogonal states, through simulation with Python3 and the Qiskit library. The research focuses on the variability of key lengths and the ability of the protocol to detect eavesdropping attempts. Results show an average key length of 14.3 bits per 100 transmitted qubits, with variability ranging from 3 to 29 bits. Detection accuracy improves significantly with sample size, achieving 95% accuracy with a sample size of 5 and 100% with a sample size of 10. These findings highlight the trade-off between key length and detection reliability, emphasizing the importance of optimization. While simulations confirm the protocol’s robustness, further studies under real-world conditions are essential. This work advances the understanding of quantum cryptographic systems and lays the foundation for secure quantum communication.